2021
DOI: 10.1186/s12885-021-08530-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective correlation between the patient microbiome with response to and development of immune-mediated adverse effects to immunotherapy in lung cancer

Abstract: Background Though the gut microbiome has been associated with efficacy of immunotherapy (ICI) in certain cancers, similar findings have not been identified for microbiomes from other body sites and their correlation to treatment response and immune related adverse events (irAEs) in lung cancer (LC) patients receiving ICIs. Methods We designed a prospective cohort study conducted from 2018 to 2020 at a single-center academic institution to assess fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Our systematic review noted these same trends across various solid tumor types receiving ICIs [ 58 ]. In addition to mirroring these findings, our research also found that increased Proteobacteria are similarly associated with decreased likelihood of irAE development [ 20 ].…”
Section: The Microbiome In Immunotherapysupporting
confidence: 67%
See 4 more Smart Citations
“…Our systematic review noted these same trends across various solid tumor types receiving ICIs [ 58 ]. In addition to mirroring these findings, our research also found that increased Proteobacteria are similarly associated with decreased likelihood of irAE development [ 20 ].…”
Section: The Microbiome In Immunotherapysupporting
confidence: 67%
“…Other studies have linked ICI outcomes in nonmelanomatous cancers to gut microbiome composition. We found a similar association between Firmicutes and ICI response in our 16S evaluation of lung cancer patients [ 20 ]; these findings were echoed in a separate cohort that had undergone whole genome shotgun sequencing [ 48 ]. Routy et al found that Akkermansia , a member of the phylum Verrucomicrobia , was enriched in NSCLC patients who responded to ICI.…”
Section: The Microbiome In Immunotherapymentioning
confidence: 60%
See 3 more Smart Citations